Pembentukan Akhlak Siswa Melalui Living Qur’an Di MTS Ira Medan - Hasibuan, Darma Syahputra; As’ad, As’ad (Kamaya: Jurnal Ilmu Agama, 2025)
Ethics today face significant challenges along with the advancement of time. This moral crisis is exacerbated by the declining role of families and the environment in providing strong moral education examples. The ethics of society is decreasing day by day, manners have disappeared in the eyes of the public, politeness is neglected, there is no longer a sense of respect between children and parents, the relationship between teachers and students has cracked, student brawls occur everywhere, all of this is caused by the decline in moral values. One effective method of shaping students' ethics is by using the living Qur'an approach. This concept emphasizes that the Qur'an is not only to be read but also must be practiced in daily life. To address this issue, an approach is needed that can be used to shape students' ethics through the living Qur'an. This research discusses the formation of students' ethics through the implementation of the living Qur'an at MTs IRA Medan. This research aims to analyze how the living Quran contributes to the formation of students' character. This study employs qualitative methods with a case study approach. Data was collected through observations, interviews, and documentation. The results indicate that the application of the living Quran at MTs IRA Medan has been integrated into learning activities and the school culture. The character development process is carried out through habituation activities such as reading the Quran before and after studying, Islamic social activities, reading Yasin/Al-Kahfi every Friday, muhadarah activities, and congregational Dhuha prayers. This program is highly effective in shaping students' character, especially supported by the role model of teachers, parental involvement, and consistency in its implementation.